1999
DOI: 10.1161/01.cir.100.22.2260
|View full text |Cite
|
Sign up to set email alerts
|

Classic Preconditioning Decreases the Harmful Accumulation of Nitric Oxide During Ischemia and Reperfusion in Rat Hearts

Abstract: Background-The role of NO in the mechanism of preconditioning is not understood. Therefore, we studied the effect of preconditioning and subsequent ischemia/reperfusion on myocardial NO content in the presence of an NO synthase (NOS) inhibitor. Methods and Results-Isolated working rat hearts were subjected to preconditioning protocols of 3 intermittent periods of rapid pacing or no-flow ischemia of 5 minutes' duration each followed by a test 30 minutes of global no-flow ischemia and 15 minutes of reperfusion. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
91
2
1

Year Published

2000
2000
2017
2017

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 124 publications
(99 citation statements)
references
References 38 publications
5
91
2
1
Order By: Relevance
“…The protective effects of Polygonum multiflorum stilbeneglycoside preconditioning in an ischemia/reperfusion model of HUVECs Li- npg a prominent role in the signaling pathway of ischemic and drug-induced preconditioning [7][8][9] . Recent studies have demonstrated that the NO produced by inducible NO synthases (iNOS) can protect the heart, and that this effect involves K + ATP channels and contractile fibers [10,11] .…”
Section: Introductionmentioning
confidence: 99%
“…The protective effects of Polygonum multiflorum stilbeneglycoside preconditioning in an ischemia/reperfusion model of HUVECs Li- npg a prominent role in the signaling pathway of ischemic and drug-induced preconditioning [7][8][9] . Recent studies have demonstrated that the NO produced by inducible NO synthases (iNOS) can protect the heart, and that this effect involves K + ATP channels and contractile fibers [10,11] .…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, although it is unlikely that an induction of arginase expression leads to a functional active enzyme within minutes our data show that we can attenuate the formation of oxidiative stress by inhibition of arginase. The most likely explanation for these acute effects are eNOS uncoupling at the time of reperfusion (10,11). Our finding that arginase-1 is strongly induced in vitro suggests that local mechanisms may trigger this increase.…”
Section: Discussionmentioning
confidence: 77%
“…However, the post-ischaemic myocardium has a characteristic loss of NO-dependent signalling (10,11). This is mainly due to an increased oxidative stress and diminished NO formation rather than the impaired downstream signalling of NO, because administration of NO donors restores a normal NO-dependent signalling (12).…”
Section: Introductionmentioning
confidence: 99%
“…Tissue acidosis occurring during ischemia increases NO production independent from eNOS [13], and even at normal pH, xanthine oxidase in the presence of low pO 2 and high nicotinamide adenine dinucleotide (NADH) concentration is capable of producing NO from nitrite [14]. Besides, in the isolated rat heart [15] and in rabbit hindlimb muscle [16], the NO concentration is still increased during ischemia after complete NOS inhibition by Nw-nitro-L-arginine (L-NNA).…”
Section: Production Of Nitric Oxidementioning
confidence: 99%